Dietetic practices in the management of childhood obesity in Malaysia - Md. Yusop, Nor Baizura (Nutrition Society of Malaysia, 2014)
Introduction: Dietitians play an essential role in the management of childhood obesity and consistency in dietetic practices is required to ensure the effectiveness of treatment. This study assessed dietitians' current practices in the management of childhood obesity, compared the practices with nutrition practice guidelines used by dietitians in other countries and identified practice components for the development of nutrition practice guidelines for the management of childhood obesity in Malaysia. Methods: A cross-sectional study was conducted among 40 dietitians in 16 Ministry of Health hospitals and three teaching hospitals. Information on current dietetic practices in the management of childhood obesity was obtained through a mailed survey questionnaire. The practices included nutritional assessment, determination of energy requirement, dietary prescription and physical activity modification. Emails were sent to 31 dietetic associations in other countries to obtain information on practice guidelines used by dietitians. Results: Frequently used dietary intervention and physical activity modification approaches were high fibre diet (65%), low fat diet (40%), reduction of sedentary pursuits and screen times (67.5%) and an increase in duration of current physical activities (60%). In comparison to other dietetic practice guidelines, the current dietetic practices in Malaysia do not usually include waist circumference, biochemical and blood pressure data. However, similar to other guidelines, the current dietetic practices included low dietary fat, high fibre diet, decreased sedentary activity and increased physical activity level. Conclusions: The dietetic practices in the management of childhood obesity in Malaysia are diverse. A comprehensive nutrition practice guideline for management of childhood obesity is urgently needed for standardisation of dietetic practices in Malaysia.